Impact of School Based Self Care Model in Assessment of Obesity and Its Risk Factor Knowledge among Urban School Children: Non Randomized Controlled Trial - Shobha S Karikatti; Praveena R Gunagi; Sunanda B Halki (Medsci Publications, 2019)
Background: A phenomenal rise [10% to 30%] has been observed in the prevalence of obesity   among adolescents. Imparting health knowledge and skills in school children can bring a huge change in healthy practices and provides an ability to take care of their health. The objectives of the study was to evaluate the impact of school based self care model in assessment of obesity and its risk factors knowledge among school children. Methodology: A Non Randomized Controlled Community trial was conducted among 480 urban school children of Belagavi. The students from intervention group [240] received school based self care model intervention over 4 weeks period. Results: In study group 80% children became aware about obesity; 60.8 % to 92.5 % gained knowledge about specific dietary factors associated with obesity and knowledge improved regarding physical activities, Using motorcycle [68.3% to 85.4%], Watching TV [62.9% to 80.4%] and Using mobiles [66.7% to 87.1%]. The proportion of students having adequate skill score increased from 27.1% to 85.9% for weight (p<0.001), 21.5% to 89.6 % for height (p <0.001) and 10% to 76.7% (p<0.001) for waist circumference after intervention. Conclusion: The school based self care model was effective as the knowledge increased by 30% and gross [50%] improvement was observed in obesity assessment skill at the end of intervention.